miRNAs and exosomes in psoriasis: coordinating cytoskeleton dynamics and extracellular matrix remodeling - Li, Sijing; Chik, Zamri; Faruqu, Farid Nazer; Mohd Hashim, Najihah; Mohd Yusof, Nor Saadah; Fernandez Alarcon, Jennifer; Ahmad, Noraini (Frontiers in Cell and Developmental Biology, 2025)
Psoriasis is a chronic inflammatory skin disorder characterized by hyperproliferation of keratinocytes, immune dysregulation, and abnormal epidermal differentiation. Its pathogenesis involves complex interactions among keratinocytes, fibroblasts, T cells, and myeloid cells, where dynamic cytoskeletal and extracellular matrix changes critically mediate intercellular communication. Emerging evidence highlights the pivotal roles of miRNAs and exosomes in coordinating these processes: miRNAs regulate cytoskeletal organization and extracellular matrix composition, while exosomes act as intercellular messengers that deliver miRNA-mediated signals, collectively shaping cell behavior and disease progression. This review synthesizes current knowledge on how miRNA-exosome networks drive cytoskeleton-extracellular matrix crosstalk in psoriasis, emphasizing their implications for cellular communication and tissue remodeling. By elucidating these mechanisms, we identify potential therapeutic opportunities to target pathogenic signaling pathways, offering new strategies for psoriasis management.